A dramatized method for teaching undergraduate students responsible research conduct. (3rd April 2023) - Chen, Kuei-Chiu; Hester, Laurel L.
ABSTRACT: Worldwide, undergraduate science and pre-medical students are encouraged to participate in authentic active learning lab work and undergraduate research experiences. Unfortunately, these experiences rarely include training in science or research ethics. Although several governmental and scientific organizations have called for increased training in responsible research conduct, relatively few studies report on the effectiveness of different pedagogical approaches. Too often science ethics socialization and training is limited to conversations with individual mentors. This paper describes how viewing an interactive theatrical presentation of several research misconduct scenarios was associated with an increase in first-year students' self-assessed understanding of the topics addressed: proper treatment of data images, respect for animal protocols, authorship considerations, and plagiarism issues. There was no decrease in self-reported responsible conduct of research (RCR) knowledge for students surveyed 10 weeks, as compared to 2 weeks, after the science ethics presentations. RCR test question scores showed only a slight decrease in correct answers from 2 to 10 weeks. Theatrical presentation is an inexpensive yet engaging approach that provides students with a chance to actively consider the importance of RCR and the complexities of contexts surrounding ethics decisions before starting a research career.